Turkic nomads and traces of their presence in the Halych-Volhynian lands in the 10th–14th centuries - Terskij, Sviatoslav (Balcanica Posnaniensia. Acta et studia, 2007)
The aim of the study is to trace the nature and effects of contacts with Turkic peoples on the territories of Halych-Volhynia, taking into account written and archaeological sources. The research method is based on an interdisciplinary approach, combining the analysis of chronicle evidence, toponymy and archaeological materials (in particular burials, amulets, weapons and horse harnesses). The results of the research confirm the significant influence of nomads on military affairs and the material culture of the region. The discovered burials, characteristic lapis lazuli amulets, copper cauldrons, bone equipment elements and arrowheads typical of steppe peoples testify to the long-term stay of Turkish groups and intensive exchange. Some of the Turks integrated into the Rus' community, which manifested itself in Christianisation, marriages and entry into the local elite. In the 13th–14th centuries, contacts intensified particularly due to the incorporation of the Halych-Volhynia state into the political and commercial system of the Golden Horde. As can be concluded, the nomadic Turkish peoples not only posed a threat to the borderlands, but also contributed to the shaping of the political structure, military organisation and cultural development of the Halych-Volhynia region.